Trends in death associated with pediatric dental sedation and general anesthesia. Issue 8 (14th June 2013) - Lee, Helen H.; Milgrom, Peter; Starks, Helene; Burke, Wylie; Cote, Charles
Summary Background Inadequate access to oral health care places children at risk of caries. Disease severity and inability to cooperate often result in treatment with general anesthesia (GA). Sedation is increasingly popular and viewed as lower risk than GA in community settings. Currently, few data are available to quantify pediatric morbidity and mortality related to dental anesthesia. Objective Summarize dental anesthesia‐related pediatric deaths described in media reports. Methods Review of media reports in the Lexis‐Nexis Academic database and a private foundation website. Settings: Dental offices, ambulatory surgery centers, and hospitals. Patients :US‐based children (≤21 years old) who died subsequently receiving anesthesia for a dental procedure between 1980–2011. Results Most deaths occurred among 2–5 year‐olds (n = 21/44), in an office setting (n = 21/44), and with a general/pediatric dentist (n = 25/44) as the anesthesia provider. In this latter group, 17 of 25 deaths were linked with a sedation anesthetic. Conclusions This series of media reports likely represent only a fraction of the overall morbidity and mortality related to dental anesthesia. These data may indicate an association between mortality and pediatric dental procedures under sedation, particularly in office settings. However, these relationships are difficult to test in the absence of a database that could provide an estimate of incidence and prevalence of morbidity and mortality. With growing numbers of children receiving anesthesia for dental procedures from providers with variable training, it is imperative to be able to track anesthesia‐related adverse outcomes. Creating a national database of adverse outcomes will enable future research to advance patient safety and quality.